Effects of Land Use Changes from Paddy Fields on Soil Bacterial Communities in a Hilly and Mountainous Area - Rokunuzzaman, Md (Microbes Environ, 2016)
Soil bacterial community structures in terraced rice fields and abandoned lands in a hilly and mountainous area were analyzed using 16S rRNA gene sequences. The DGGE band patterns of each soil were similar. Based on pyrosequencing data, the richness and diversity of bacterial species were slightly higher in paddy fields than in other soils. A beta-diversity analysis clearly indicated that the bacterial community structure in paddy fields differed from those in non-paddy field lands and crop fields that had not been used as a paddy field. These results may reflect the history of land use.